The Flouting of Cooperative Principles in Little Women by Louisa May Alcott - Fauziah Rachmita Suwandi; Ahmad Idris Asmarandhani; Linda Mayasari (Tell : Teaching of English Language and Literature Journal, 2015)
This research aims to find out flouting of cooperative principles maxim which are employed by the characters and to find out the speaker’s meaning in Little Women novel by Louisa May Alcott.There are two objectives of the research that must be answered; (1) to describe the flouting of cooperative principles in Little Women by Louisa May Alcott; (2) to find of the possible reason for flouting the maxims in the Little Women novel by Louisa May Alcott. Descriptive qualitative is applied as the method of the research. Discourse Analysis proposed by H.P Grice is used as the main approach and Flouting Cooperative Principles Levinson is applied as the supporting theory. The results of the analysis it can be concluded that the fact of flouting of maxim is the important point in linguistics and pragmatics. English learner should improve themselves by understanding flouting of maxims. We can find the flouting maxim of relation in script movie or the other object like short story, script drama and novel.